Research hotspots and frontiers of preconditioning in cerebral ischemia: A bibliometric analysis - Long Zhang; Xue Zhou; Jing Zhao; Xingchen Wang (Heliyon, 2024)
Background: Preconditioning is a promising strategy against ischemic brain injury, and numerous studies in vitro and in vivo have demonstrated its neuroprotective effects. However, at present there is no bibliometric analysis of preconditioning in cerebral ischemia. Therefore, a comprehensive overview of the current status, hot spots, and emerging trends in this research field is necessary. Materials and methods: Studies on preconditioning in cerebral ischemia from January 1999–December 2022 were retrieved from the Web of Science Core Collection (WOSCC) database. CiteSpace was used for data mining and visual analysis. Results: A total of 1738 papers on preconditioning in cerebral ischemia were included in the study. The annual publications showed an upwards and then downwards trend but currently remain high in terms of annual publications. The US was the leading country, followed by China, the most active country in recent years. Capital Medical University published the largest number of articles. Perez-Pinzon, Miguel A contributed the most publications, while KITAGAWA K was the most cited author. The focus of the study covered three areas: (1) relevant diseases and experimental models, (2) types of preconditioning and stimuli, and (3) mechanisms of ischemic tolerance. Remote ischemic preconditioning, preconditioning of mesenchymal stem cells (MSCs), and inflammation are the frontiers of research in this field. Conclusion: Our study provides a visual and scientific overview of research on preconditioning in cerebral ischemia, providing valuable information and new directions for researchers.